Supply Chain Management of Perishable Food Products: A Strategy to Achieve Competitive Advantage through Knowledge Management - Singh, Nityanand; Javadekar, Prachee (Indian Journal of Marketing, 2011)
Supply-chain management of perishable food products is a very typical issue, which is to be adequately managed to gain the competitive advantage for optimum profit in the current scenario. In today's era of modern marketing where competition is on the peak level, supply chain integration is the only way left, which not only provides satisfaction to consumers in terms of price and quality, but also provides an opportunity to reduce the cost of the product by minimizing wastage and also offers reasonable price to the farmer for their produce. The information technology enabled services, i.e. ITES is an important component of knowledge management, which integrates the various functions of the supply chain and helps the organization to do real time business. In western/developed western/developed countries, the development of retail has taken place only due to advent integration of supply-chain management by way of implementing the IT infrastructure. This paper focuses on the uses of ITES by the Un-organized retailers for supply-chain management of perishable food products in Pune. The paper provides insight on the integration of various functions of SCM by taking the help of ITES, its cost implication and complexities of function. The major findings of this paper are can be summarized as there is no use of ITES for supply-chain management of perishable food products by un-organized retailers at Pune, which is the area of concern as it contributes as good as 72% loss of perishable food products in terms of quality and 35% wastage in terms of quantity. It is recommended that the use of information technology enabled services by Un-organized retailers would make them competitive and strengthen their capabilities to sustain their business in front of giant organized retailers. This will also regulate the un-necessary fluctuation in prices of perishable food products in the long run.